Metal-doped silicate and phosphate glasses for antibacterial dental biomaterials - Haruaki Kitagawa; Tomoki Kohno; Fan Deng; Gabriela L Abe; Hirohiko Sakai; Yo-Shiuan Fan; Tingyi Wu; Jun-ichi Sasaki; Satoshi Imazato (Medical Journals Sweden, 2023)
AbstractOwing to the development of glass 45S5 (Bioglass®) comprising 45 mol% SiO2, 24.5 mol% Na2O, 24.5 mol% CaO, and 6 mol% P2O5, different compositions of silicate glasses have been developed. When these silicate glasses contact an aqueous environment, such as body fluids, they induce apatite layer formation on their surfaces owing to ion exchange. In addition to promoting hard tissue formation, researchers have sought to enhance the antibacterial properties of these glasses, thereby resulting in the development of metal-doped silicate glasses. The addition of antibacterial metals (silver, copper, zinc, and gallium) to silicate glass offers a promising avenue for combating oral pathogens. In recent years, there has been growing interest in metal-doped phosphate glasses. The release of metal ions can be regulated by modifying the dissolution rate of the phosphate glasses. This review summarizes the metal-doped silicate and phosphate glasses that confer antibacterial activity. Future strategies for the development of dental biomaterials that incorporate metal-doped glass and exhibit antibacterial effects are discussed.